Volume characterisation of the electrical discharge - Lungu, Cristian Victor; Hnatiuc, Bogdan (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
In this paper, theoretical and practical study of gliding arc discharges is presented considering the discharge itself. The characteristics of the gliding arc are studied at different flow rate values. For this study case instrumental air was used in order to elongate the spark thus obtaining the gliding arc. The comparison took into consideration linear approximations of the discharge compared to the real phenomena.